Peluang yang Dapat Diraih oleh Desa Patimban dari Pembangunan Pelabuhan Patimban - Ahmad Gozali; Tarlani; Ernawati (Jurnal Riset Perencanaan Wilayah dan Kota, 2023)
Abstract. Infrastructure development is one of the pillars of the state capital. The efforts made by the government in the National Strategic Project are the development of the Rebana Triangle Area. This development is expected to become the center of an industrial area in West Java with an area of 54,000 ha. The construction of the Patimban Port project is one of the government's strategies in reducing capacity at the Tanjung Priok Port. The development of Patimban Port is planned to use 542 ha of land in Patimban, with details of 300 ha of land and 242 ha of sea reclamation. Seeing the enormous potential and opportunities that exist at the Patimban port, the local government needs special efforts to prepare superior human resources so that they can respond to the opportunities that come from the presence of the Patimban port. to see readiness, this study uses the Community Readiness Model (CRM) method. From the results of the analysis, it can be seen that the opportunities from the Patimban port can be utilized by the local community and from the perspective of the readiness of the government and the local community. Abstrak. Perkembangan infrastruktur menjadi salah satu sebagai penyangga ibukota negara. Upaya yang dilakukan pemerintah dalam Proyek Strategis Nasional yaitu pengembangan Kawasan Segitiga. Pengembangan ini diharapkan dapat menjadi sentra Kawasan industri di Jawa Barat dengan luas 54,000 ha. Pembangunan proyek Pelabuhan Patimban merupakan salah satu dari strategi pemerintah dalam mengurangi kapasitas di Pelabuhan Tanjung Priuk. Pembangunan pelabuhan patimban direncanakan menggunakan lahan di patimban seluas 542 ha dengan detailnya 300 ha daratan dan 242 ha reklamasi laut. Melihat begitu besarnya potensi dan peluang yang ada di pelabuhan patimban, pemerintah setempat perlu adanya upaya khusus dalam menyiapkan SDM yang unggul agar dapat menjawab peluang dari hadirnya pelabuhan patimban. untuk melihat kesiapan, penelitian ini menggunakan metode Community Readiness Model (CRM). Dari hasil analisis dapat dilihat peluang dari pelabuhan patimban yang dapat dimanfaatkan oleh masyarakat setempat serta melihat dari sisi kesiapan pemerintah dan masyarakat setempat.